Between the Influence of Customary, Dutch, and Islamic Law: Jaksa Pepitu and Their Place in Cirebon Sultanate History - Tendi Tendi; Djoko Marihandono; Abdurakhman Abdurakhman (Al-Jami'ah Research Centre, 2019)
The field of law is an interesting matter in the study of Indonesian history. The meddling of the various elements of culture and tradition due to political dynamics and power in the nation’s history, making law in Indonesia one type of hybrid entity. The interference of the law was not only seen from its legal products, but also from the bodies given the responsibility to enforce the law at that time. One of the prosecutors’ agency that had existed in the past was Jaksa Pepitu. This study aims to reveal the origins of the Jaksa Pepitu, elaborate on their works in the field of law in Cirebon environment, and describe the legal influences that contributed to the color of this collegial council. By way of historical research methodology and narrative approach, it can be seen that the prosecutor’s council is the agency essential in the practice of law. They were linked to Cirebon princes and can be appointed through VOC approval. In addition, the actions of the prosecutors can be seen from the position, independence, and authority they have. The various things surrounding the Jaksa Pepitu indicate that it is legal institution influenced by customary, Western and Islamic laws. [Bidang hukum menjadi hal yang menarik dalam kajian sejarah Indonesia. Percampuran pelbagai unsur budaya dan tradisi akibat adanya dinamika politik dan kekuasaan dalam perjalanan bangsa, membuat hukum di Indonesia menjadi salah satu jenis hukum yang bersifat hybrid. Percampuran hukum itu tidak hanya dilihat dari produk hukum yang dihasilkan, namun juga dapat ditelisik dari badan yang diberi tanggung jawab untuk menegakkan hukum pada masa itu. Salah satu badan jaksa yang pernah eksis di masa lalu adalah Jaksa Pepitu. Studi ini bertujuan untuk mengungkapkan asal muasal Jaksa Pepitu, menguraikan kiprahnya dalam bidang hukum di lingkungan Cirebon, dan mendeskripsikan pengaruh-pengaruh hukum yang turut memberi warna dewan kolegial ini. Dengan metodologi penelitian sejarah dan pendekatan naratif yang dilakukan, dapat diketahui bahwa dewan jaksa itu merupakan badan penanggung jawab bidang hukum. Mereka memiliki keterkaitan dengan para pangeran Cirebon dan dapat diangkat dengan persetujuan VOC. Selain itu, kiprah para jaksa ini dapat dilihat dari posisi, independensi, dan wewenang yang mereka miliki. Adapun pelbagai hal yang mengitari Jaksa Pepitu menunjukkan bahwa mereka ini adalah badan yang dipengaruhi oleh hukum adat, Barat, dan Islam.]